Implementasi Kebijakan Disiplin Pegawai Negeri Sipil Di Balai Latihan Kerja Mandiri Provinsi Jawa Barat - Anggara, Sahya; Nur, Mohamad Ichsana; Daroni, Ahmad (Publica: Jurnal Pemikiran Administrasi Negara, 2018)
The purpose of this study was to determine the policy implementation of Government Regulation Number 53 of 2010 concerning Discipline of Civil Servants at the Independent Training Center of West Java Province. The method in this reseach used is descriptive qualitative method. In this study, researchers examined the implementation of policy, the researchers used the theory of policy implementation model Edward III in Widodo (2017) about four factors that play an important role in achieving successful implementation, namely communication, resources, disposition, and bureaucratic structure. Data were obtained through observation, interviews, documentation, and library studies and using data analysis techniques according to Miles and Huberman. The results of the study, the Implementation of Government Regulation Number 53 of 2010 concerning Discipline of Civil Servants at the West Java Provincial Independent Training Center has not run optimally. First, communication has gone well because of the distribution of the regulations to the staff. Second, the resources are not optimal because the number of human resources in the West Java Province Independent Training Center is still lacking and the preparedness needs to be improved. Third, the disposition has been well seen from the willingness of the Employees to attend the morning rally, obey working hours, and carry out tasks responsibly. Fourth, the bureaucratic structure has been effective because the West Java Provincial Training Center already has Standard Operating Procedures and clear fragmentation procedures.